2022
DOI: 10.1017/jfm.2022.259
|View full text |Cite
|
Sign up to set email alerts
|

Interface instabilities in Faraday waves of two-layer liquids with free surface

Abstract: For a fluid system with an interface between two-layer liquids and a free surface, there exist two series of natural frequencies. Under vertical excitations, the interface and the free surface can be excited separately or simultaneously. Laboratory experiments were conducted to excite the first- and second-mode Faraday waves on the free surface, which forced the in-phase motion of the interface. The experimental data were used to validate the extended numerical model NEWTANK. The secondary surface instability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 32 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…They also discussed the effect of individual depth of layers on Faraday instability, in which lower layer depth does not play any role after a certain limit (Li et al 2018c). Liu and Lin (2022) have done similar experiments along with three-dimensional numerical simulations on a three-fluid system. They observed that it is possible to have two different modes at either interface, which can lead to reverse flow between the fluids and leads to Kelvin-Helmholtz type (KH-type) instability.…”
Section: Introductionmentioning
confidence: 99%
“…They also discussed the effect of individual depth of layers on Faraday instability, in which lower layer depth does not play any role after a certain limit (Li et al 2018c). Liu and Lin (2022) have done similar experiments along with three-dimensional numerical simulations on a three-fluid system. They observed that it is possible to have two different modes at either interface, which can lead to reverse flow between the fluids and leads to Kelvin-Helmholtz type (KH-type) instability.…”
Section: Introductionmentioning
confidence: 99%